Mouse-derived Synaptosomes Trypsin Cleavage Assay to Characterize Synaptic Protein Sub-localization - Jasmeet Shergill; Domenico Azarnia Tehran (Bio-Protocol)
Neurons communicate through neurotransmission at highly specialized junctions called synapses. Each neuron forms numerous synaptic connections, consisting of presynaptic and postsynaptic terminals. Upon the arrival of an action potential, neurotransmitters are released from the presynaptic site and diffuse across the synaptic cleft to bind specialized receptors at the postsynaptic terminal. This process is tightly regulated by several proteins at both presynaptic and postsynaptic sites. The localization, abundance, and function of these proteins are essential for productive neurotransmission and are often affected in neurological and neurodegenerative disorders. Here, we outline a method for purifying mouse synaptosomes and using limited tryptic digestion to assess the subcellular localization of synaptic proteins. During synaptosomes purification, presynaptic terminals reseal and are protected from proteolysis, while postsynaptic proteins remain susceptible to tryptic cleavage. These changes can easily be evaluated by western blot analysis. This approach offers a straightforward and reliable method to evaluate the subcellular localization of synaptic proteins based on their proteolytic sensitivity, providing valuable insights into synaptic physiology and pathology.